Evaluating Gender Equity in The Berenstain Bears Picture Books - Tisnawijaya, Christy; Kurniati, Geni (Bahasa dan Seni: Jurnal Bahasa, Sastra, Seni, dan Pengajarannya, 2026)
Picture books serve as a foundational medium in early childhood education, utilizing interrelated visual and verbal elements to foster linguistic, cognitive, and social development. Despite their pedagogical utility, certain literary works inadvertently perpetuate traditional gender roles, constraining children's conceptualizations of identity. This study evaluates gender representation within eleven selected titles of The Berenstain Bears series. Employing a qualitative multimodal content analysis, the study integrates Butler's gender performativity framework (1990), Callow's multimodal narrative approach (2020), and Adam and Harper's evaluative criteria (2021) to examine how domestic, social, and recreational roles are constructed. This study offers novelty by establishing a dual-lens multimodal framework that bridges visual semiotics and social performativity to interrogate subtle gendered subtexts in popular picture books. The verbal and visual evidence reveals a distinct structural dichotomy: while the narratives convey essential moral and behavioral lessons, they simultaneously reinforce restrictive gender stereotypes by casting maternal figures in perpetual caregiving roles and paternal figures as aggressive or financially dominant providers. Concurrently, instances of gender equity emerge through shared domestic responsibilities and non-gendered sports participation. These findings highlight the necessity for educators and parents to critically engage with early childhood texts, cultivating critical visual literacy to mitigate the internalization of biased gender constructs.